Pengaruh Struktur Modal dan Profitabilitas Terhadap Nilai Perusahaan - Listia Aulia Indy; Rismawati Rismawati (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The purpose of this study is to analyze and determine the effect of capital structure and profitability on firm value. This research employed a quantitative descriptive approach. Data were obtained from the annual reports of basic chemical companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period, using purposive sampling. Data analysis used SPSS Version 26. The results indicate that capital structure and profitability influences firm value.